The History of Geographic Information Systems: Perspectives from the Pioneers - Nestor L. Osorio (Issues in Science and Technology Librarianship)
This article reviews the book The History of Geographic Information Systems: Perspectives from the Pioneers. Timothy Foresman, editor. Prentice Hall, 1998.